The Effect of Fringe Benefits on Employment Fluctuations in U.S. Automobile Manufacturing - Smyth, David J.; Karlson, Stephen H. (The Review of Economics and Statistics, 1991)
David J. Smyth, Stephen H. Karlson, The Effect of Fringe Benefits on Employment Fluctuations in U.S. Automobile Manufacturing, The Review of Economics and Statistics, Vol. 73, No. 1 (Feb., 1991), pp. 40-49